Adventures of Huckleberry Finn - Twain, Mark; Kazin, Alfred (New York : Bantam books, 1981)
A photographic facsimile of the first issue of the first edition, in 1885, of the adventures of a young boy traveling down the Mississippi River with an escaped slave.
Keywords: Finn, Huckleberry (Fictitious character) -- Fiction; Runaway children -- Fiction; Male friendship -- Fiction; Fugitive slaves -- Fiction; Race relations -- Fiction; Boys -- Fiction; Voyages and travels -- Fiction; Slavery -- Fiction